Pengembangan Aplikasi Perangkat Bergerak Pelayanan dan Pusat Informasi Penduduk Desa (Studi Kasus: Desa Sumberrejo) - Dina Noviana; Agi Putra Kharisma; Mahardeka Tri Ananta (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The progress of the village and its inhabitants is one of the goals of village empowerment where managing and serving the interests of the population is the obligation of the village government. Based on the type of village services provided in Sumberrejo village, several problems were found, including the process of recap and integration of daily resident data that had to be done twice, the lack of knowledge of the population regarding the submission of letter administration, and the process of disseminating social assistance information which was not coordinated so that it was less accurate and detailed. The service application and village information center were built for the Android platform with mail submission services, daily population data collection, and access to social assistance information in order to achieve equitable population welfare. In this study, the Prototyping method is used to produce an application that can accommodate changes in the development process based on feedback provided by stakeholders and users at the evaluation stage. Based on the results of the implementation carried out using the Kotlin programming language and Firebase database, black box testing has been carried out with 100% valid results, compatibility testing with 100% compatible results for Android SDK levels 21 to 32, and usability testing with an average SUS value ( The final System Usability Scale for residents is 91.5, for RT heads it is 85.5 and for village administrative staff it is 83, where each is included in grade A+, Best Imaginable status, and Acceptable category.